Basic Training for Local Tour Guides to Strengthen Community-Based Tourism in Desa Teluk Jambi - Masita, Ella; Mukminin, Amirul; Hidayat, Marzul; Fortunasari; Gowon, Muhammad; Iqroni, David; Waldo, Kevin (Jurnal Karya Abdi Masyarakat, 2026)
Community-based tourism (CBT) development requires not only the availability of natural and cultural resources but also adequate local human resources capable of managing and delivering meaningful tourism experiences. One of the key challenges faced by many rural areas in Indonesia is the limited capacity of local communities, particularly the absence of trained local tour guides. Desa Teluk possesses significant agro-tourism and nature-based tourism potential; however, this potential has not been optimally utilized due to low tourism awareness and limited guiding competencies. This article reports the implementation and outcomes of a university-led community service program aimed at strengthening community readiness through basic local tour guide training. The program employed a participatory approach involving village officials, youth organizations, POKDARWIS, and MSME. Findings indicate notable improvements in participants’ understanding of tour guiding roles, communication skills, and service standards. Overall, the program strengthened community readiness for sustainable tourism development.